Relationship between uterine veins, ureter, and hypogastric nerve for uterine transplantation: An anatomic study. Issue 8 (31st March 2022) - Robin, Fabien; Dion, Ludivine; Lavoue, Vincent; Goujon, Anna; Boudjema, Karim; Sulpice, Laurent; Morandi, Xavier; Nyangoh Timoh, Krystel
Abstract: Uterine transplantation is on the rise worldwide. In contrast to its arterial anatomy, venous drainage of the uterus is poorly defined in the literature. Our aim was to provide a standardized description of uterine veins through a multimodal approach to establish anatomical landmarks for the uterine transplantation surgeon. Data were obtained from: (1) an anatomical study of eight fresh female cadavers (16 hemipelves) studied separately by an extra fascial dissection from the iliac bifurcation to the uterine pedicle, with analysis of the urinary tract and nerve structures and (2) a virtual anatomical study from the Anatomage® Table comprising a high‐fidelity virtual reconstruction of two deceased female subjects by imaging and anatomical methods. An inconstant duality of uterine veins was identified: a deep uterine vein of larger caliber and a superficial uterine vein observed in 25% of cases. A close relationship of the ureter passing posterior to the superficial uterine vein and anterior to the deep uterine vein was evident in the parametrium. The inferior hypogastric plexus was identified in all cases immediately behind the deep uterine vein. The data obtained from the fresh female cadavers were validated by the Anatomage® Table. We describe the close relationship of the uterine veins with the ureter and the inferior hypogastric plexus. This knowledge represents a surgical landmark to support the success of uterine transplantation by respecting both the graft and the safety of the living donor by limiting the risk of injuries during uterus procurement.